2016
DOI: 10.1080/13683500.2016.1194812
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of travellers’ repurchase behaviour for luxury cruise product

Abstract: This study proposed and tested a theoretical model in which image congruence, affect, satisfaction, switching costs, and trust have an influence on travellers' decision to repurchase a luxury cruise product by considering the moderating impact of conspicuousness. The model was evaluated using a quantitative approach. The original model included a satisfactory fit and prediction power. The results of the structural analysis revealed that the hypothesized associations between the study variables were generally s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 68 publications
(130 reference statements)
0
15
0
Order By: Relevance
“…Also, customer satisfaction of the cruise service had a positive impact on customer loyalty [11]. In addition, customer satisfaction significantly influenced repurchase intention through the positive impact of switching cost and trust [29].…”
Section: Satisfaction With a Cruise Line And Its Relationships With Bmentioning
confidence: 97%
See 3 more Smart Citations
“…Also, customer satisfaction of the cruise service had a positive impact on customer loyalty [11]. In addition, customer satisfaction significantly influenced repurchase intention through the positive impact of switching cost and trust [29].…”
Section: Satisfaction With a Cruise Line And Its Relationships With Bmentioning
confidence: 97%
“…In regards to the cruise industry, Han and Hyun [28] revealed that overall company image was positively associated with desire toward cruise travel and repeat cruising intention. Also, Han et al [29] attempted to discover a more divided version of image congruence into social image congruence and ideal social image congruence. In their study, the image congruence showed a positive relation with affect and customer satisfaction.…”
Section: Cruise Line Image and Its Part In Satisfaction And Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…Transaction-specific customer satisfaction occurs after the product is consumed and involves an evaluation of one specific purchase (Oliver, 1980(Oliver, , 1993. Cumulative customer satisfaction is a consumer's comprehensive evaluation of product purchases and subsequent consumption over time (Fornell, 1992;Han et al, 2018;Johnson and Fornell, 1991;Nguyen et al, 2018). Cumulative customer satisfaction is argued to be more valuable than transaction-specific satisfaction when predicting consumer buying behavior, as well as the performance of the organization (Fornell et al, 1996;Johnson et al, 2001;Nguyen et al., 2018).…”
Section: Customer Satisfactionmentioning
confidence: 99%